PENYELESAIAN HUKUM PEMERIKSA PROVOS TERHADAP ANGGOTA POLRI YANG MELAKUKAN TINDAK PIDANA DENGAN PENERAPAN RESTORATIVE JUSTICE DI WILAYAH HUKUM POLDA DIY - Adi Sumarwan (Kajian Hukum, 2022)
The legal resolution of the Provos' examination of members of the National Police in criminal acts by applying restorative justice in the Yogyakarta Regional Police Legal Area is carried out by continuing to use restorative justice as follows criminal cases that have already been carried out with restorative justice. The implementation of restorative justice must still meet the specified requirements, namely material requirements and formal requirements. Obstacles in carrying out legal settlements carried out by the Provost Examiner against Police Members in criminal acts by implementing restorative justice in the Yogyakarta Regional Police Legal Area. There are five (5) obstacles that have been encountered by the Provost Examiner, namely not finding common ground between the reporter and the Police member who carried out the action. crimes, irregular fulfillment of administrative requirements in submitting restorative justice, lack of support from members' superiors, lack of budget in implementing restorative justice, and lack of training for Provos members in resolving restorative justice in criminal cases committed by members of the National Police.